Determinantes socioeconômicas da distribuição espacial de painéis fotovoltáicos residenciais no Brasil - Sabadini, Felipe (2019)
The environmental situation demands new forms of energy generation; the current energy matrix is dependent on fossil fuels that besides its harmful potential is also a non-renewable natural resource. Sensitive to this change, the Brazilian government published ANEEL's normative resolution 482/2012, which established the conditions for the exchange of energy between micro-generators. The current scenario shows that besides the environmental benefits, other motivations and barriers are also raised by the literature as motivations that lead to the adoption of photovoltaic panels. This work tries to fill part of this gap, being the first to examine the influence of socioeconomic factors on the spatial distribution of residential photovoltaic panels in Brazilian municipalities taking into account the spatial factor as a determinant. A cross-section model was elaborated, and spatial models of data in SAR and SEM panels were also used. The results found in this work demonstrate influences of the spatial variable as well as population; GDP of agribusiness and salary. Demonstrating convergence with previous studies, the best model was the spatial error for presenting better indexes, the spatial variable and peer effects showed a significant influence on the adoption of panels.